2015
DOI: 10.1073/pnas.1509488112
|View full text |Cite
|
Sign up to set email alerts
|

The pH low insertion peptide pHLIP Variant 3 as a novel marker of acidic malignant lesions

Abstract: Current strategies for early detection of breast and other cancers are limited in part because some lesions identified as potentially malignant do not develop into aggressive tumors. Acid pH has been suggested as a key characteristic of aggressive tumors that might distinguish aggressive lesions from more indolent pathology. We therefore investigated the novel class of molecules, pH low insertion peptides (pHLIPs), as markers of low pH in tumor allografts and of malignant lesions in a mouse model of spontaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 56 publications
1
53
0
Order By: Relevance
“…The pHLIP peptides find a wide range of applications in biomedical sciences 16,2022,43,44 and, also, they prove to be a very convenient model system for the investigation of polypeptide insertion into the lipid bilayer of a membrane triggered by pH. 12,28 Whereas various spectroscopic methods applied previously probed changes in the conformation of peptides, SAXS employed in this study allowed us, for the first time, to monitor the changes in the liposome and lipid bilayer structure.…”
Section: Discussionmentioning
confidence: 99%
“…The pHLIP peptides find a wide range of applications in biomedical sciences 16,2022,43,44 and, also, they prove to be a very convenient model system for the investigation of polypeptide insertion into the lipid bilayer of a membrane triggered by pH. 12,28 Whereas various spectroscopic methods applied previously probed changes in the conformation of peptides, SAXS employed in this study allowed us, for the first time, to monitor the changes in the liposome and lipid bilayer structure.…”
Section: Discussionmentioning
confidence: 99%
“…The targeting of primary tumors by pHLIP ® peptides and delivery imaging and therapeutic agents has been demonstrated on more than 10 varieties of human and murine tumors [1517], including lymphoma [18], pancreatic [19], breast [2021] and prostate [22] transgenic mouse models and human head/neck biopsy samples [2324]. It was confirmed that tumor targeting by pHLIP ® peptides is indeed pH-dependent and could be modulated by bicarbonate and glucose, which affects tumor acidity [15, 2021, 2526]. Three pHLIP ® variants, WT, Var3 and Va7 were selected as lead candidates for pH-specific delivery of imaging and therapeutic agents to tumors of different origins [10, 16, 1921].…”
Section: Introductionmentioning
confidence: 99%
“…It was confirmed that tumor targeting by pHLIP ® peptides is indeed pH-dependent and could be modulated by bicarbonate and glucose, which affects tumor acidity [15, 2021, 2526]. Three pHLIP ® variants, WT, Var3 and Va7 were selected as lead candidates for pH-specific delivery of imaging and therapeutic agents to tumors of different origins [10, 16, 1921]. …”
Section: Introductionmentioning
confidence: 99%
“…Studies in which the pH of the surface of tumors was monitored showed that the regions of the highest tumor invasion (see Glossary) corresponded to areas of highest acidity [10]. Therefore, targeting the most acidic regions of tumors is especially beneficial because the most acidic regions are the most aggressive [11]. …”
Section: Extracellular Aciditymentioning
confidence: 99%